CO2 Laser-Assisted Sclerectomy vs. Microcatheter-Assisted Trabeculotomy in the Management of a Bilateral Congenital Ectropion Uveae With Glaucoma: A Case Report and Literature Review - Min Chen; Min Chen; Yuhang Li; Yuhang Li; Bo Cheng; Bo Cheng; Qi Zhang; Qi Zhang; Xin Liu; Xin Liu; Kaijun Wang; Kaijun Wang (Frontiers in Medicine, 2022)
IntroductionBilateral congenital ectropion uveae (CEU) is rare syndrome, usually accompanied by refractory glaucoma. Proper and timely treatment was very important for the prognosis. The report aims to compare the long-term outcomes and complications between the two eyes after different approaches of surgery in a case of bilateral CEU with advanced glaucoma.Case PresentationThe patient was a 20-year-old male with bilateral CEU and glaucoma. The intraocular pressure (IOP) was 48 mm Hg in the right eye (OD) and 52 mm Hg in the left eye (OS). The vertical cup-to-disc (C/D) ratio was nearly 1.0 in both eyes. Despite maximum medical therapy, the target IOP could not be achieved. Therefore, CO2 laser-assisted sclerectomy surgery (CLASS) was performed in OS, and the IOP was remarkably decreased. 1 month after the surgery, the IOP rebounded slightly and was controlled with a fixed-combination anti-glaucoma medicine. 3-month postoperatively, a YAG laser goniopuncture (LGP) was performed to enhance the IOP-lowing effect and the anti-glaucoma agent was discontinued. An ab externo microcatheter-assisted trabeculotomy (MAT) was performed in OD, and the IOP was also significantly decreased. During the follow-up period, the IOP was well controlled for both eyes without any medication. Shallow anterior chamber and complicated cataract developed in OS after CLASS, and there was no obvious late complication in OD after MAT.ConclusionsTo our knowledge, this was the first attempt to perform two different surgeries, CLASS and MAT, in both eyes of a single patient presented with bilateral CEU with glaucoma. Our results showed that the IOP was lower after CLASS, but there were potential complications such as shallow anterior chamber and complicated cataract. MAT could achieve a moderate IOP-lowing effect but had a higher safety. CLASS and MAT may be considered effective surgical options for the management of such patients.